Mindfulness as a factor in reducing turnover intention in sales employees (the role of work stress and resilience in the process) - Alexander Abraham Daeng Kuma; Henndy Ginting (Goodwood Publishing, 2025)
Purpose: This study aims to examine the role of mindfulness in reducing turnover intention through work stress, and how resilience moderates this relationship among sales employees in Indonesia’s distribution industry. Methodology/approach: Data were collected from 307 sales professionals through purposive sampling, consisting of employees with at least one year of tenure. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. Results/findings: Results indicate that mindfulness significantly reduces turnover intention by lowering work stress. Work stress fully mediates the relationship between mindfulness and turnover intention. Furthermore, resilience significantly moderates the relationship between mindfulness and work stress, strengthening the stress-reducing impact of mindfulness. Conclusions: Mindfulness plays a critical role in decreasing employees' intention to leave by alleviating work stress, and resilience enhances this effect. Organizations are encouraged to implement structured mindfulness training programs and resilience-building workshops as part of their employee development strategies to mitigate stress-related turnover. Limitations: The study was conducted using samples and populations from only one company and was limited to the sales department. Contribution: This study contributes to the development of HRD management practices by introducing individual interventions focused on mindfulness and resilience. It provides new psychological approaches to reduce turnover caused by work stress.